No association between anatomic factors and non-contact ACL injury risk in 217 female team sport players: a prospective 4.5-year study - Leppänen, M.; Jarske, H.; Krosshaug, T.; Myklebust, G.; Vasankari, T.; Parkkari, J.; Pasanen, K. (Scandinavian Journal of Medicine & Science in Sports, 2026)
The purpose of this explorative study was to investigate the association between anatomic factors and risk for non-contact anterior cruciate ligament (ACL) injuries among female team sport players. A total of 225 players from basketball, floorball, and volleyball aged 12-38 years (median 16) participated in baseline physical examination including measurements of static knee and pelvic alignment, leg length, pelvic width, and femoral and tibial condyle widths. Players were then prospectively followed for new ACL injuries for 2.5-4.5 years. Legs were analyzed separately. After excluding eight players with a history of ACL injury, the final sample included 217 players and 434 legs. Associations between variables of interest and ACL injury risk were analyzed using generalized linear mixed models with binomial distribution and player and club as random effects. During the follow-up, 20 new non-contact ACL injuries were registered. None of the measures investigated showed a significant relationship with the risk of new non-contact ACL injuries. In conclusion, anatomic factors showed no association with increased risk of ACL injury in female team sport players.